Evaporation of water droplets in the 1st stage of the ultrasonic spray pyrolysis device - Ternik, Primož; Rudolf, Rebeka (Anali PAZU, 2022)
he present work deals with numerical modelling of aerosol evaporation in the flow of carrier gas (N2) in the 1st stage of ultrasonic spray pyrolysis device. For that we have used so called Euler-Lagrange approach, where the gas phase is treated as a continuous phase by solving the Navier-Stokes equations, while the dispersed phase is treated as a number of discrete particles, which exchange energy, momentum and mass with the continuous phase. Results are presented for the temperature field of carrier gas and water vapor, as well as for the droplets’ diameter, temperature and evaporation time.
Keywords: Evaporation; Numerical modelling; Euler-Lagrange approach; Water droplets